Philadelphia chromosome negative myeloproliferative neoplasms at Chris Hani Baragwanath academic hospital - Mayet, Yusuf (My University, 2016)
BACKGROUND Myeloproliferative Neoplasms (MPN) are a heterogeneous group of diseases that are characterized by clonal proliferation of the erythroid, myeloid, or megakaryocytic lineages. The discovery of the JAK2 V617F mutation has provided new insights into the disease and has broadened the therapeutic landscape. The management of MPN is aimed at relieving symptoms of disease, managing and modifying the signs of disease, and preventing complications. There is a lack of data with regard to MPN in South Africa and this study attempts to understand this disease entity as represented by patients at a large public sector hospital. PATIENTS AND METHODS This study is a retrospective review of adult patients seen at the Clinical Haematology Unit, Department of Internal Medicine at Chris Hani Baragwanath Academic Hospital during the period 01/01/1987 to 31/12/2011. The aim of the study was to determine the profile of patients diagnosed with Polycythaemia Vera (PV), Essential Thrombocythaemia (ET), and Primary Myelofibrosis (PMF), and in particular to describe the demographics, clinical presentation, management, and outcomes of patients with MPN. RESULTS AND DISCUSSION A total of 94 patients were analyzed of which 37% were diagnosed with ET, 18% were PV, and 45% PMF. The median age of presentation was 63, 54, and 64 for ET, PV, and PMF respectively with a female to male ratio of 1.24:1 for all patients. Fatigue, weight loss, and pruritus were the most common presenting symptoms, while splenomegaly was found in 80% of patients and was the predominant clinical manifestation. It was noted that hydroxyurea was the most important form of cytoreductive therapy used, especially in ET where 91% received it. Venesection was performed in 100% of PV patients. JAK2 V617F mutation testing became available in 2006 and of all the patients tested, 100% (ET), and 89 %( PV), and 89 %( PMF) were positive. Only 5% of patients achieved a complete response whilst on the treatment available. Transformation to acute myeloid leukaemia was shown in 9% of the patients, whilst 22% ultimately resulting in death. CONCLUSION Ph1 chromosome negative MPN in South Africa is an uncommon disease which most commonly occurs in the 55 to 65 year old age group. Overall, it is slightly more common in females compared to males, with particular reference to ET. PMF is the most common Ph1 chromosome negative MPN, followed by ET and PV. Patients with Ph1 chromosome negative MPN present typically with fatigue, constitutional symptoms and splenomegaly. Presentation to hospital with thrombotic events and bleeding was also significant. The mainstay of treatment is variable, depending on the nature of the MPN i.e. venesection for PV, and hydroxyurea for ET and PMF. Complications such as arterial and venous thrombosis, bleeding and leukaemic transformation occurred at a similar rate to that described in the literature. JAK2 V617F mutation investigation was available since 2005, and 93% of all patients that were tested, proved to have the mutation. More frequent and routine testing of this mutation is needed in the future. Other treatment options such as anagrelide, interferon alpha, and JAK inhibitors were used at a very low frequency in our population of MPN patients. The prognosis of patients correlates with other studies of MPN, with PMF showing the worst prognosis and lowest median overall survival rate, and the highest transformation rate to acute leukaemia. More widespread use of JAK2 inhibitors in the future may impact favourably on the adverse prognosis and poor survival.
A Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirement for the degree of Master of Medicine (MMed) Johannesburg, 2015